Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1152/jn.00237.2018
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of muscle and cortical response scaling to balance perturbation acceleration

Abstract: The role of cortical activity in standing balance is unclear. Here we tested whether perturbation-evoked cortical responses share sensory input with simultaneous balance-correcting muscle responses. We hypothesized that the acceleration-dependent somatosensory signals that drive the initial burst of the muscle automatic postural response also drive the simultaneous perturbation-evoked cortical N1 response. We measured in healthy young adults ( n = 16) the initial burst of the muscle automatic postural response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(80 citation statements)
references
References 43 publications
(89 reference statements)
4
71
0
3
Order By: Relevance
“…As in the previous study (Quant et al 2005;Payne et al 2018; Payne and Ting 2020a), the ERPs of P1, N1, P2 and N2 were confirmed around the Cz electrode ( Fig. 1I and 3-top).…”
Section: Eeg Responses Revealed By Erp and Erspsupporting
confidence: 86%
See 1 more Smart Citation
“…As in the previous study (Quant et al 2005;Payne et al 2018; Payne and Ting 2020a), the ERPs of P1, N1, P2 and N2 were confirmed around the Cz electrode ( Fig. 1I and 3-top).…”
Section: Eeg Responses Revealed By Erp and Erspsupporting
confidence: 86%
“…Payne et al have been working to characterize the N1 and other ERPs during perturbed stance in recent years. They showed that: (1) people with lower balance ability exhibited larger N1 responses compared to those with better balance control (Payne and Ting 2020a); and (2) N1 includes startle responses in addition to balancecorrecting motor responses (Payne et al 2018). In addition, they also showed abnormal N2 activity in PD patients (Payne and Ting 2020b), where N2 is induced with a latency of about 400 ms with much smaller amplitudes compared to N1, suggesting that later components might be less reflexive and more supraspinal-network-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to error‐related and error‐correcting muscle activity, balance perturbations elicit error‐related cortical activity resembling the ERN (Figure ). Specifically, a frontocentral negativity called the balance N1 is evoked simultaneous to the balance‐correcting muscle activity (Payne, Hajcak, & Ting, ). The balance N1 is a negative peak of cortical activity occurring between 100–200 ms after balance perturbation at frontal and central midline EEG electrodes (Fz, FCz, Cz; Marlin et al, ; Mierau, Hulsdunker, & Struder, ), with amplitudes large enough to observe on single trials (Mierau et al, ; Payne et al, ).…”
Section: Balance Perturbations and The Balance N1mentioning
confidence: 99%
“…Specifically, a frontocentral negativity called the balance N1 is evoked simultaneous to the balance‐correcting muscle activity (Payne, Hajcak, & Ting, ). The balance N1 is a negative peak of cortical activity occurring between 100–200 ms after balance perturbation at frontal and central midline EEG electrodes (Fz, FCz, Cz; Marlin et al, ; Mierau, Hulsdunker, & Struder, ), with amplitudes large enough to observe on single trials (Mierau et al, ; Payne et al, ). The balance N1 has been localized to the supplementary motor area (Marlin et al, ; Mierau et al, ), but theories of its function are extremely limited.…”
Section: Balance Perturbations and The Balance N1mentioning
confidence: 99%
See 1 more Smart Citation